2023
DOI: 10.1037/pas0001279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of diagnosing limited prosocial emotions in young children using the Clinical Assessment of Prosocial Emotions (CAPE).

Bryan Neo,
Georgette E. Fleming,
Silvana Kaouar
et al.

Abstract: This study evaluated the interrater reliability, convergent and divergent validity, incremental validity, and clinical prognostic utility of the Clinical Assessment of Prosocial Emotions (CAPE; Frick, 2013) for assessing limited prosocial emotions (LPE). Participants were 232 young children (Mage = 3.94 years, SD = 1.46, range = 2–8; 74.6% boys) clinic-referred for conduct problems. We scored the CAPE using binary and dimensional scoring approaches and measured outcomes using parent-report and child laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…In the present study, we showed that scores from the CAPE were also substantially correlated with ratings of CU traits on the ICU. Also, consistent with past research (Hawes et al, 2020; Molinuevo et al, 2020; Neo et al, 2023), we found that scores from the CAPE were correlated with measures of conduct problems and aggression. Of note, we also demonstrated the CAPE scores were associated with aggression, even when controlling for CD symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, we showed that scores from the CAPE were also substantially correlated with ratings of CU traits on the ICU. Also, consistent with past research (Hawes et al, 2020; Molinuevo et al, 2020; Neo et al, 2023), we found that scores from the CAPE were correlated with measures of conduct problems and aggression. Of note, we also demonstrated the CAPE scores were associated with aggression, even when controlling for CD symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, the current results, along with past findings (Hawes et al, 2020; Molinuevo et al, 2020; Neo et al, 2023) support cautious use of the CAPE in clinical assessments and the continued development and testing of its psychometric properties. Of most importance, the current findings suggest that CAPE scores predicted clinically important constructs, even after controlling for the level of CU traits obtained on behavior ratings.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations